A formação da dama higiênica. A educação feminina em teses médicas da Faculdade de Medicina da Bahia na segunda metade do século XIX (1851-1898) - Alencar, Juselice Alves Araujo de (2021)
This research has as its goal to understand the sense of prescriptions concerning the feminine education in theses written and upheld by doctors of the Faculdade de Medicina da Bahia (Medicine Faculty of Bahia), in the second half of the 19th century, specifically during the period of 1851 to 1898, which corresponds respectively to the years of defence of the first and the last identified and analysed thesis. The following specific goals were proposed: To investigate the nature of educational prescriptions found in the medical theses; to analyse similarities and/or divergences in the medical-hygienic discourse; to interpret the reach and social spaces for which these prescriptions were addressed. I used the historiographic approach of Roger Cartier (1990, 1991, 1992) as of the notion of representation to understand how the social relations are woven in each epoch. As a result of documental research, 12 medical theses (19th century) were identified, selected, collected and analysed from the archive of the Biblioteca Gonçalo Moniz / Memória da Saúde Brasileira (Gonçalo Moniz Library / Brazilian Health Memory), of the Faculdade de Medicina da Bahia / UFBA (Medicine Faculty of Bahia / UFBA). The doctors who authored the doctoral theses built a discourse regarding the women’s education that resulted in hygienic prescriptions concerning behaviour rules, pregnancy and marriage hygiene, breastfeeding, health care, in order to regulate women’s manners and behaviours at the home space (family) and at other social spaces.